2012
DOI: 10.3747/pdi.2011.00096
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lymphatic Vessels in Patients with Encapsulating Peritoneal Sclerosis

Abstract: ♦ Background: The angiogenic response is partly involved in the progression of encapsulating peritoneal sclerosis (EPS). However, the details of the angiogenic response, especially for lymphatic vessels in patients with EPS, remain unclear. In addition, because of technical limitations, morphology studies reported to date have examined only the parietal peritoneum. The morphologies of parietal and visceral lymphatic vessels in patients with EPS both need to be analyzed. ♦ Methods: We examined peritoneal sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…There may be some pathophysiological differences between visceral and parietal peritoneum, although they have not been fully established so far. Yaginuma et al demonstrated increased lymphatic vessels in visceral peritoneum rather than parietal peritoneum [26], and this difference might be related to the susceptibility of encapsulating membrane formation in visceral peritoneum via increased exudation. The histological stage may also indicate the consequences of NFMs, that is progression to encapsulation and adhesion or scar formation without the development of EPS.…”
Section: Definition Of Nfm and Its Histological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…There may be some pathophysiological differences between visceral and parietal peritoneum, although they have not been fully established so far. Yaginuma et al demonstrated increased lymphatic vessels in visceral peritoneum rather than parietal peritoneum [26], and this difference might be related to the susceptibility of encapsulating membrane formation in visceral peritoneum via increased exudation. The histological stage may also indicate the consequences of NFMs, that is progression to encapsulation and adhesion or scar formation without the development of EPS.…”
Section: Definition Of Nfm and Its Histological Featuresmentioning
confidence: 99%
“…This protein is involved in cell motility, migration, and proliferation during development, in the immune system, and in cancer [31]. Because EPS develops in association with increased accumulation of serum and high concentrations of fibrin [17,32], secretion of cytokines and growth factors [26,[33][34][35] may activate the transformation of peritoneal mesenchymal cells into swollen fibroblast-like cells that highly express podoplanin on their cell membranes. Podoplanin-positive fibroblast-like cells in the peritoneum of EPS patients may be activated by platelets and inflammatory cells expressing podoplanin-ligand, CLEC-2 [30], and by the surrounding extracellular matrix containing hyaluronic acid [31].…”
Section: Significance Of Podoplanin Expression In New Membranesmentioning
confidence: 99%
“…The vascular network of parietal peritoneum is mainly located between the submesothelial interstitial layer and peritoneal adipose tissue and is composed of small artery, arteriole, capillary, post-capillary venule and veins ( Figure 1A-b), occasionally with lymphatic vessels. Of note is that the vascular population varies dependent on age and mesothelial location; blood and lymph vessel density in parietal peritoneum is higher in infant age [17], lymphatic vessels are more abundant in the visceral peritoneum than the parietal [19,25].…”
Section: Terminology Concerning Pd Peritoneal Pathology Parietal Perimentioning
confidence: 99%
“…To identify vessels or lymph vessels, cluster of differentiation (CD) 31 (or CD34) and podoplanin staining is added to the procedure [16,17]. Podoplanin staining is also useful to identify mesothelial cells, or podoplanin positive fibroblasts or "fibroblast-like cells (FLC)" [18,19]. Preparation of frozen specimens and electron microscope specimens is recommended when precise investigations are required for special cases or for research purposes.…”
Section: Procedures Of Peritoneal Biopsy and Sample Processingmentioning
confidence: 99%
“…These kidney-specimens were stained with anti-GLCCI1 antibody (rabbit primary antibody (pAB), 1:50; Abcam, Cambridge, UK; catalog ab171137), and anti-CD34 antibody, used as specific endothelial marker (rabbit pAB, 1:500; Abcam, Cambridge, UK; catalog ab81289). Immunohistochemical staining was performed as described previously [22]. Reaction products were visualized by staining with 3, 3-diaminobenzidine tetrahydrochloride, before counter-staining sections with Periodic-Acid-Schiff.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%